‘“Un train peut en cacher un autre…”: Entretien avec Arnaud Rykner. Propos recueillis par Helena Duffy’ - Helena Duffy; Arnaud Rykner (Pennsylvania State University Press, 2022)
The interview with Arnaud Rykner, French novelist, playwright, and Professor of French and Theatre Studies at the Sorbonne–Nouvelle in Paris, focuses on the author’s novel, Le Wagon (2010), recently translated into English by Sue Boswell as The Last Train(to be published in 2020 by Snuggly Books). Based on the experience of the deportation of the author’s great uncle as well as on archival sources, the novel retraces the journey of the train numbered 7907 from the transit camp of Compiègne to the concentration camp of Dachau in July 1944. The narrative describes the unhuman conditions in which the deportees travelled, and which consisted of excruciating heat, overcrowding, lack of food and drink, and the violence that unsurprisingly ensued in such circumstances. During the nearly three–day journey, a quarter of those who had originally boarded the train perished. In the interview with Helena Duffy, Rykner talks about the genesis of his book, the ethics of writing about the Holocaust in the post–witness era, and the phenomenon of the so–called ‘Jonathan Littell Generation’ with which he identifies.